Poster Solution Suggestopedia Method Test for Manager for Company Candidates in Law and Finance Aspects about Corruption Phenomenon - Pamuji, Wirawan; Simangunsong, Rini T; Murtaza.ZD; Feryliyan, Achmad; Suriadi, Mimin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The phenomenon of corruption is inevitable in company-related crime and delinquency, and it can affect the entire system by reducing normal funds and capital, hindering progress in advancing any company globally. Therefore, candidates for managerial positions rely on tests that reveal their true personalities and their ability to manage the company effectively. Research and development methods are used to design a test, referred to as the poster method, which assesses how candidates address issues of corruption among staff, particularly in finance and legal aspects, using a literature-based approach. In fact, the test is designed to create transparency in managers' handling of corrupt or fraudulent staff, with a focus on analyzing methods for eliminating corruption within the company.